Continuous preperitoneal infusion of ropivacaine for postoperative analgesia in patients undergoing major abdominal or pelvic surgeries. A prospective controlled randomized study - Reem Abdelraouf ElSharkawy; Tamer Elmetwally Farahat; Khaled Abdelwahab (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: This study was conducted to compare continuous preperitoneal infusion (CPI) with continuous epidural infusion (CEI) of ropivacaine for pain relief and effect on pulmonary functions after major abdominal and pelvic surgeries. Material and Methods: One hundred patients were randomized into two equal groups. Patients in CPI group (n = 50) received analgesia by continuous infusion of 0.2% ropivacaine, whereas those in the CEI group (n = 50) received continuous epidural infusion of 0.2% ropivacaine. The primary outcome was the first request of analgesia. The secondary outcome was the influence on the pulmonary functions. Results: The time for the first request of analgesia was longer in the CPI group compared with that in the CEI group (7.3 ± 1.6 vs. 4.1 ± 1.1 h with P value = 0.001). The daily dose of morphine was lesser in CPI versus CEI group (11.3 ± 1 against 17.4 ± 0.9 mg). The pulmonary function tests were comparable except peak expiratory flow rate, which was better in CPI (170 ± 5.4) than CEI group (148.1 ± 5.8; with P value = 0.001). Conclusion: Continuous preperitoneal infusion provides a superior analgesic effect than the continuous epidural infusion as regards delayed first request of analgesia, better pain scores, lesser usage of additional analgesics with better respiratory function.